2019
DOI: 10.1017/dmp.2018.157
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Disease-Related Stigma During Infectious Disease Outbreaks

Abstract: Outbreaks of emerging infectious disease are a constant threat. In the last 10 years, there have been outbreaks of 2009 influenza A (H1N1), Ebola virus disease, and Zika virus. Stigma associated with infectious disease can be a barrier to adopting healthy behaviors, leading to more severe health problems, ongoing disease transmission, and difficulty controlling infectious disease outbreaks. Much has been learned about infectious disease and stigma in the context of nearly 4 decades of the human immunodeficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
129
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 37 publications
7
129
0
6
Order By: Relevance
“…Feeling discriminated was a pertinent issue encountered by COVID-19 patients, which is consistent with previous studies that highlighted the stigma experienced by infected patients 46 who may be shunned by their loved ones, friends, and communities for being a carrier of the virus, or as part of a nationality or ethnic group that contributed to its transmission 47 . In addition, internalized stigma may also occur in which infected people view themselves as inferior to others, which leads to self-loathing as a result of their disease status 48,49 .…”
Section: Discussionsupporting
confidence: 87%
“…Feeling discriminated was a pertinent issue encountered by COVID-19 patients, which is consistent with previous studies that highlighted the stigma experienced by infected patients 46 who may be shunned by their loved ones, friends, and communities for being a carrier of the virus, or as part of a nationality or ethnic group that contributed to its transmission 47 . In addition, internalized stigma may also occur in which infected people view themselves as inferior to others, which leads to self-loathing as a result of their disease status 48,49 .…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with Wu et al (2020) who reported that medical professionals who were not specialized in infectious disease experienced greater pressure when facing infected patients. Another dimension to infection risk exposure is stigmatization where people may consider HCWs a movable source of infection in the community (Fischer et al 2019), so stigmatization was a significant stressor for nurses of ZFH. On the other hand, although employing strict biosecurity measures is a must to prevent spread of infection to self and others, it was a significant stressor for nurses of ZFH.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to strengthen trust and enhanced communications between patients and healthcare professionals to deliver accurate ZIKV information and to discuss sensitive topics, such as condom use or a possible termination of pregnancy, as well as the need to work on the de-stigmatization of the infection among the general population. Infectious-disease related stigma, such as leprosy, HIV/AIDS, tuberculosis, ZIKV, or COVID-19 could be a barrier to adopt health behaviors, leading to an increased transmission and difficulties to control outbreaks [ 33 ]. Studies have shown how Central and South American populations living in Spain experience ethnic discrimination, affecting their psycho-social health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%